2018
DOI: 10.3389/fphar.2018.00649
|View full text |Cite
|
Sign up to set email alerts
|

Bevacizumab Diminishes Inflammation in an Acute Endotoxin-Induced Uveitis Model

Abstract: Introduction: Uveitis is an eye disease characterized by inflammation of the uvea and an early and exhaustive diagnosis is essential for its treatment. The aim of our study is to assess the potential toxicity and anti-inflammatory efficacy of Bevacizumab in an experimental uveitis model by subcutaneously injecting lipopolysaccharide into Lewis rats and to clarify its mechanism.Material and Methods: Blood–aqueous barrier integrity was assessed 24 h after endotoxin-induced uveitis (EIU) by analyzing two paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 79 publications
(87 reference statements)
1
10
1
Order By: Relevance
“…To investigate the mechanisms responsible for these effects, we used LPS-stimulated RAW 264.7 cells as an in vitro model. Consistent with the in vivo study and previous reports, ( McMenamin and Crewe, 1995;Behar-Cohen et al, 1998;Mérida et al, 2018) the levels of IL-6 and TNF-α were increased in the supernatants of murine macrophages stimulated with LPS, while KS23 prevented the production of these inflammatory markers. This result is consistent with previous reports that APN suppresses TNF-α and IL-6 production and their biological effects in adipocytes, macrophages and endothelial cells (Shibata et al, 2015).…”
Section: Disscusionsupporting
confidence: 92%
See 2 more Smart Citations
“…To investigate the mechanisms responsible for these effects, we used LPS-stimulated RAW 264.7 cells as an in vitro model. Consistent with the in vivo study and previous reports, ( McMenamin and Crewe, 1995;Behar-Cohen et al, 1998;Mérida et al, 2018) the levels of IL-6 and TNF-α were increased in the supernatants of murine macrophages stimulated with LPS, while KS23 prevented the production of these inflammatory markers. This result is consistent with previous reports that APN suppresses TNF-α and IL-6 production and their biological effects in adipocytes, macrophages and endothelial cells (Shibata et al, 2015).…”
Section: Disscusionsupporting
confidence: 92%
“…EIU is a commonly used model of human acute anterior uveitis characterized by the breakdown of the blood-eye barrier, with macrophages and neutrophils leaving the iris area and infiltrating the anterior chamber, along with the induction of various cytokines and other inflammatory mediators ( de Vos et al, 1994 ; Mérida et al, 2018 ). Clinical and histopathological evaluations have shown that KS23 inhibited LPS-induced blood-eye barrier destruction, manifested as protein and cell leakage into the eye.…”
Section: Disscusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ocular inflammation is one of the main causes of blindness and visual disturbance [1,2]. Uveitis is a sight threatening disease that results from acute, recurrent, or chronic inflammation of the uvea [1] and is involved with the immune system [3,4]. Despite aggressive treatment, chronic recurrence can be detrimental and cause irreversible visual impairment and blindness.…”
Section: Introductionmentioning
confidence: 99%
“…About 50% of the cases are associated with chronic systemic inflammatory diseases [8] such as rheumatoid arthritis [9], systemic lupus erythematosus [10], polyarteritis nodosa, relapsing polychondritis, Wegner's granulomatosis, scleroderma, Bechet's disease [11], and ankylosing spondylitis [12][13][14]. Endotoxin induced uveitis (EIU), a well established animal model for human acute anterior uveitis, is induced by lipopolysaccharide (LPS), which is released from Gram-negative bacteria [1,12]. LPS is specifically recognized by toll-like receptor 4 (TLR4) [4], a pattern recognition receptor of the innate immune system on the surface of macrophages [3,5,15].…”
Section: Introductionmentioning
confidence: 99%